OPTIMIZATION OF INFRASTRUCTURE IN CLOUD-BASED SAAS QUEUE SYSTEM DEVELOPMENT - Rey Shazni Helmi, Muhammad
Stability and performance are crucial pillars in supporting the success of an e-commerce website. Instability and crashes can reduce user interest and negatively impact sales. Moreover, page loading speed plays a vital role in determining sales conversion rates. This